Побудова довірчих інтервалів для ваг альтернатив рішень на основі експертних оцінок парних порівнянь - Nedashkovskaya, N. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The method for evaluation of confidence intervals for weights of decision alternatives on the basis of pairwise comparison judgments, made by an expert, is proposed in the paper. The method is based on an assertion, that expert pairwise comparison judgments represent real ratios of weights of decision alternatives only to some extent and contain the uncertainty, independently of their consistency level. It is supposed that this uncertainty is caused by Saaty scale and such personal qualities of an expert as pessimism and optimism when providing pairwise comparisons. The method is based on the theory of trust (evidence) and results of computer modeling of randomly filled pairwise comparison matrices. The resulted confidence intervals reflect real weights of decision alternatives more reliably in contrast with crisp weights given by the famous analytic hierarchy process. Using com-puter modeling, the resulted confidence intervals are compared with results obtained by known fuzzy prioritization methods.